Using Diffusion-Diffusion Exchange Spectroscopy to observe diffusion exchange in yeast - Breen-Norris, James O; Siow, Bernard; Hipwell, Ben; Roberts, Thomas; Lythgoe, Mark F.; Ianus, Andrada; Alexander, Daniel C.; Walker-Samuel, Simon (Diffusion Fundamentals, 2019)
The permeability of cell membranes varies significantly across both healthy and diseased tissue, and changes in cell membrane permeability can occur during treatment response in tumours. Measurements of cell membrane permeability could therefore be useful for tumour detection and as biomarkers of treatment response in the clinic. As the diffusion of water across the cell membrane is directly dependent on cell membrane permeability, we have investigated the ability of diffusion-diffusion exchange spectroscopy to quantify the diffusion exchange of water in a suspension of yeast, as a first step towards its application in tumours.